Needs Analysis of English for Business Communication in the Maritime and Tourism Industries: A Case Study on Developing Digital-Based ESP Teaching Strategies at Politeknik eLBajo Commodus - Jufidah; Indra Ratna Sari; Maria Beatrix Rahinart Wellalangi (Jurnal Penelitian Terapan Mahasiswa, 2025)
This study investigates the need for English language skills in business communication within the maritime and tourism industries of Labuan Bajo, focusing on the development of digital-based English for Specific Purposes (ESP) teaching strategies through a case study in the English Terms for Business and Professional course at Politeknik eLBajo Commodus. It addresses challenges faced by 12 first-semester students in distinguishing bargaining (competitive, price-focused) from negotiation (collaborative, value-added), essential for professional communication in maritime contracts and tourism packages. Using a qualitative case study design integrated with action research, the study conducted semi-structured interviews with 5 industry stakeholders and discourse analysis of 10 authentic business documents to identify priority skills, followed by a 4-week trial of a digital ESP module using Zoom simulations and AI chatbots. Results revealed significant improvements: 92% of students correctly differentiated bargaining and negotiation, 75% enhanced their negotiation speaking skills, and 83% improved in business writing. These findings highlight the effectiveness of digital tools in bridging curriculum gaps and aligning vocational education with industry needs in Labuan Bajo’s tourism-driven economy.